Students’ Collaborative Performance through STEM Topic “Led Card – Light It Up” For 8th Grade - Le Hai My, Ngan; Mai Ha Phuong, Uyen; Nguyen Thi Kim, Anh (Universitas Negeri Semarang, 2025)
STEM education has become a crucial strategy for improving students’ collaborative competence by engaging them in hands-on, problem-based learning. Integrating STEM topics into natural science curricula remains limited in many countries, including Vietnam. To address this gap, this study aimed to design and implement a STEM lesson titled “LED Card – LIGHT IT UP” for 8th-grade students to develop collaborative competence and deepen their understanding of power sources and simple circuits. The study employed a quasi-experimental design with 21 students participating in three sessions, each lasting 45 minutes. Students worked in small groups and engaged in collaborative activities using techniques such as Numbered Heads Together, Brainstorming, Placemat, Gallery Walk, and XYZ. All group interactions during these activities were observed and video-recorded. The collected data were then qualitatively analyzed based on predefined collaboration criteria, including role assignment, idea exchange, feedback provision, and joint problem-solving, to assess each group’s level of collaboration. The results revealed that four out of five groups consistently demonstrated effective collaboration, particularly during reporting and design review sessions, despite facing challenges in online coordination. In conclusion, the integrated STEM lesson effectively enhanced students’ collaborative competence while deepening their understanding of fundamental electrical concepts. The results also highlighted some limitations, such as student distractions and unequal contributions among members, indicating the need for improvements in techniques and teacher guidance methods to enhance the effectiveness of group activities in STEM topics. The novelty of this study lies in its innovative synthesis of established collaborative teaching techniques within a STEM framework, providing a promising approach for enhancing secondary education.